Application of Pareto’s Method in Analysing Postal Service Quality - Kovač-Striko, Elizabeta; Rakić, Estera; Andabaka, Goranka (Promet - Traffic&Transportation, 2012)
The basic aim of control in postal traffic is to insure high-quality se1vices for customers. The paper presents the analysisof quality control in collecting postal items, based on the dataobtained during the control performed by the internal ControlService in the postal centre for international traffic Zagreb. Thepaper also offers some measures for the improvement of thequality of services.